Cross shelf gradients of scleractinian corals in the Spermonde Islands, South Sulawesi, Indonesia - SYAFYUDIN YUSUF; MARIA BEGER; Asmi Citra Malina A.R. Tassakka; MAARTEN DE BRAUWER; AMANDA PRICELLA; RAHMI RAHMI; WIDYASTUTI UMAR; GINO V. LIMMON; ABIGAIL MARY MOORE; Jamaluddin Jompa (Society for Indonesian Biodiversity, 2021)
Abstract. Yusuf S, Beger M, Tassakka ACMAR, Brauwer MD, Pricella A, Rahmi, Umar W, Limmon GV, Moore AM, Jompa J. 2021. Cross shelf gradients of scleractinian corals in the Spermonde Islands, South Sulawesi, Indonesia. Biodiversitas 22: 1415-1423. Coral reef ecosystems around the world have suffered extensive degradation, including the reefs of the Wallacea region within the Coral Triangle global biodiversity hotspot. Anthropogenic and natural threats can reduce the level of coral reef biodiversity differentially across environmental or impact gradients. The purpose of this study was to evaluate the changes in hard coral (Scleractinia) diversity and community structure across an inshore-offshore zonation gradient in the Spermonde Islands, South Sulawesi, Indonesia. Data on coral colony species and abundance as well as live coral cover were collected from 10 m2 belt transects at a depth of 6 to 8 m. A total of 72 transects were placed around the 12 island stations in three zones: the inner mid-shelf zone, outer mid-shelf zone and outer shelf zone. Data were analyzed to determine the species richness, and three ecological indices for the hard coral communities were calculated: the Shannon Diversity Index (H'), Similarity Index (E), and Dominance Index (C). A total of 310 hard coral species belonging to 62 genera were recorded. The coral communities were dominated by the genera Fungia, Montipora and Porites, and coral cover was in the 'moderate' category. The number of species was directly proportional to the number of colonies within each zone. Live coral cover was higher in the inner mid-shelf zone and outer shelf zone than the outer mid-shelf zone; conversely, the species richness and coral colony abundance were higher in the outer mid-shelf zone. However, the differences were not statistically significant. The indices H’, C, and E did not differ significantly between the zones. However, Tambakulu Island in Zone 4 had the lowest values of E and H’ and the highest value of C. Findings suggest that most-hard coral communities in the cross-shelf zones of the Spermonde Islands are stable communities characterized by relatively high diversity and low dominance indices.